2007
DOI: 10.1007/s10286-007-0437-9
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane anesthesia decreases cardiac vagal activity and heart rate variability

Abstract: We evaluated cardiac vagal activity during sevoflurane anesthesia in neurosurgical patients. Heart rate variability was determined by power spectral analysis and entropy with the patient awake and during sevoflurane anesthesia. High frequency power (0.15-0.50 Hz) and heart rate entropy decreased during sevoflurane and these effects were significantly correlated (r = 0.71 +/- 0.12, P < 0.05). The results confirm that cardiac vagal activity was the primary determinant of heart rate variability, which was attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…[11] Paisansathan demonstrated that sevoflurane anesthesia decreased cardiac vagal activity and heart rate variability. [12]…”
Section: Discussionmentioning
confidence: 99%
“…[11] Paisansathan demonstrated that sevoflurane anesthesia decreased cardiac vagal activity and heart rate variability. [12]…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that general anesthesia may influence HRV 45, 46. Thus, to maintain comparability, anesthesia was carried out in accord with a standardized protocol, and bispectral index (BIS) monitoring was applied in both groups 47.…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane decreased LF, but not HF and LF/HF, except for at the lower bispectral index (BIS) values (BIS 40) where LF/HF decreased in a study by Kanaya et al [10]. Therefore, in deep sevoflurane anaesthesia, as also shown in other studies [6,7], both cardiac sympathetic and parasympathetic activity decreased, although the decrease was larger in parasympathetic activity [7].…”
Section: Discussionmentioning
confidence: 61%